Losing the battle; The marginalization of Javanese compact forms - Munandar, Aris (Wacana, Journal of the Humanities of Indonesia, 2018)
In the contact situation with Indonesian, the standard variety of Javanese in Yogyakarta is experiencing an incipient shift. The shift is indicated by the shrinking domain of use, and the degradation of speakers’ proficiency. It also reveals some ongoing changes in its structure, observable in the tendency of the younger generation to use particular elements different to those used by grandparent and parent generations. This article examines unique patterns of Javanese morphosyntax by focusing on the suffix -a, infix -um-, -in-, and confix ka-an, on the basis of utterances recorded from authentic speech events involving speakers of different generations. The findings show a gradual replacement of these affixes by a more general morphosyntax pattern similar to that of Indonesian. It concludes that the suffix -a and infix -um-, -in- exhibit low resistance to the imposition of Indonesian. It also predicts that in future Javanese will show more convergent with Indonesian because of the marginalization of unique patterns of Javanese morphosyntax.